COMPREHENSIVENESS OF PHYSIOTHERAPY INTERVENTION TO PREVENT FALL IN DIABETIC NEUROPATHY PATIENT AT Dr. H ARJONO S PONOROGO HOSPITAL: A CASE REPORT - Kingkinnarti, K; Rahayu, Umi Budi (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Diabetic Neuropathy has a negative impact on leg and ankle function (Strength and flexibility) which in itself affect the patients’s physical activity and quality of life. Physiotherapy protocols aimed at increasing intrinsic and extrinsic leg muscle strenght maybe a promosing approach to improve lower extremity function , prevent further complications and improve the patient's activities of dayli living.. Case Presentation: A 65-years old patients with diagnosis of Diabetic N europathy ,came to the Medical Rehabilitation Installation at RSUD Dr Hardjono Ponorogo with complains of burning sensation,tingling and numbness in both leg. Genu varus was seen in both legs,decreased right leg muscle strength,sensory los on feeling of touch,pain and temperature in both legs from the toes to the lower border of the knee. Management and Outcome: Aerobic Exercise, flexibility exercise, strengthening and balance exercise as well as gait training are given to patient with Diabetic Neuropathy. Exercise is given 3 times a week for 4 week. The measuring instrument uses Time Up And Go Test where it is reported that after undergoing comprehensive exercise therapy there is decreased in the TUG score from a score 22 second to score 19 second which means there is an increase in the patients static and dinamic’s balance. Discussion: Ankle exercises theraphy has also shown good results for improving ankle Range Of Motion and Diabetic Neuropathy symptoms as well as for redistributing plantar pressure during movement. Interventions in the form of strengthening, stretching, balance and gait training are very useful in preventing foot ulcers and amputations, reducing the risk of falls, increasing daily physical activity and quality of life, all of which can be beneficial in reducing mortality and comorbidities.. Conclusion: Combining Exercise therapy in the form of aerobic exercise, flexibility exercise, strengthening and balance exercise for the lower limbs, and gait training is beneficial in increasing muscle strength, balance and gait so that it can reduce the risk off falling in diabetic neuropathy patient.